Ownership of Land: Legal Philosophy and Culture Analysis of Land Property Rights - Fuad, Fokky; Tardjono, Heriyono; Machmud, Aris; Rohayah, Nizla; Maghucu, Prosper (Jurnal Media Hukum, 2000)
Land stands as a fundamental aspect of human existence, serving as a cornerstone for meeting diverse needs and holding considerable economic significance. Its limited capacity often becomes a trigger for societal conflicts, spanning both vertical and horizontal dimensions. A well-crafted land policy holds the potential to foster community prosperity and ensure environmental sustainability. However, the imposition of state-driven evictions often leads to agrarian conflicts, undermining customary rights. This study examines the intricate relationship between land and humanity through the lenses of legal philosophy and the concept of land property rights within legal culture. Employing a formative juridical research approach, the authors aim to uncover a comprehensive human understanding rooted in philosophical perspectives, legal theory, dogmatic legal norms, and legal culture. From a philosophical standpoint, land represents a space where the spiritual connection between humans and their divine entities takes form. Furthermore, within the realm of legal culture, land is perceived as an integral part of the human essence, symbolizing the place of birth, growth, mortality, and final resting.